Takedown: the pursuit and capture of Kevin Mitnick, America's most wanted computer outlaw - by the man who did it - Shimomura, Tsutomu (Hyperion, 1996)
An international computer security expert offers a suspenseful account of his pursuit and eventual capture of hacker Kevin Mitnick, describing his high-tech face-off with the world's most notorious cyberthief. The dramatic true story of the capture of the world's most wanted cyberthief by brilliant computer expert Tsutomu Shimomura, describes Kevin Mitnick's long computer crime spree, which involved millions of dollars in credit card numbers and corporate trade secrets. Reprint. NYT.